2022
DOI: 10.1093/jnen/nlac036
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Detection of IDH1 Mutation With Cell-Free Circulating Tumor DNA and D-2-Hydroxyglutarate, D/L-2-Hydroxyglutarate Ratio in Gliomas

Abstract: Isocitrate dehydrogenase-1 (IDH1) mutation is accepted as one of the earliest events in tumorigenesis in gliomas. This mutation causes preferential accumulation of D- relative to L-enantiomer of 2-hydroxyglutarate (2-HG). Minimally invasive techniques to detect IDH1 mutation may prove useful for clinical practice. We adopted 2 different diagnostic approaches to detect IDH1 mutation status in glioma patients: Evaluation of D- and L-2-HG levels in cerebrospinal fluid (CSF), urine, and plasma, and identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…17 This translates to improved mutation detection rates in CSF, including epidermal growth factor receptor in BrM and glioblastoma (GBM), 18,19 MYD88 in primary CNSL (PCNSL), 20 and IDH1 in gliomas (Data Supplement). 21 This improved performance with CSF also holds true for protein and miRNA biomarkers (Data Supplement).…”
Section: Why Choose Csf Over Plasma?mentioning
confidence: 81%
See 1 more Smart Citation
“…17 This translates to improved mutation detection rates in CSF, including epidermal growth factor receptor in BrM and glioblastoma (GBM), 18,19 MYD88 in primary CNSL (PCNSL), 20 and IDH1 in gliomas (Data Supplement). 21 This improved performance with CSF also holds true for protein and miRNA biomarkers (Data Supplement).…”
Section: Why Choose Csf Over Plasma?mentioning
confidence: 81%
“…In IDH-mutant gliomas, D-2HG levels are elevated in CSF, but not in serum or urine (Data Supplement, Table S8). 21,63,81 Despite variable diagnostic performance (AUROC, 0.701-0.934), CSF D-2HG levels are more sensitive to IDH-mutant status than the detection of IDH1 mutations in CSF (Table 2). 21,81 CSF D-2HG levels also correlate with IDH-mutant tumor volume, 81 thereby enabling surveillance of tumor progression in addition to diagnosis of IDH-mutant gliomas.…”
Section: Cns Malignancy Biomarkersmentioning
confidence: 99%
“…In cases where a biopsy is risky or not feasible, CSF ctDNA can capitalize on this molecular approach and provide a less invasive means of arriving at a specific diagnosis, which will then have therapeutic and prognostic implications. Several studies have preliminarily demonstrated the feasibility of classifying gliomas using CSF ctDNA data, in particular in regard to IDH [ 6 , [61] , [62] , [63] , [64] ] and H3 mutations [ [61] , [62] , [63] , 65 , 66 ]; H3 K27M-mutant diffuse midline gliomas are an especially interesting target for this approach, as their location frequently makes surgical access difficult. It is important to note that many of these studies utilized intracranial CSF (obtained intraoperatively or from a ventricular shunt or reservoir), and the diagnostic sensitivity of a lumbar puncture may be lower [66] .…”
Section: Circulating Tumor Dna (Ctdna)mentioning
confidence: 99%
“…In addition, in the case of metastatic tumors, this physical proximity may be the key to obtaining information specific to the CNS compartment: CNS metastases may have a different genomic evolution than the primary tumors they derive from [2] , which—due to the blood-brain barrier—may not be appropriately captured by liquid biopsies in plasma, but can be detected in CSF. Lastly, CSF has a low baseline cellularity that notably decreases the “noise” that needs to be filtered to detect true tumor material, and numerous studies directly comparing CSF and plasma samples have demonstrated a higher yield for the detection of tumor genomic material in CSF [3] , [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various approaches have been developed, including "liquid biopsies" (nucleic acid extracted from biological fluids such as plasma, urine, and cerebrospinal fluid (CSF)) for detecting the IDH mutation (Satomi et al, 2022); D2HG detection in body fluids; and advanced MRI imaging with specific D2HG detection by magnetic resonance spectroscopy (MRS) (Fujita et al, 2022;Mithraprabhu et al, 2021;Tuna et al, 2022). However, none of them is currently used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%